Familial clustering and risk of groin hernia in children. Issue 2 (26th July 2017) - Burcharth, J.; Pedersen, M.; Bisgaard, T.; Pedersen, C. B.; Rosenberg, J.
Abstract: Background: The hypothesis was that groin hernias are hereditary. This study was undertaken to establish the degree of familial clustering of groin hernias on a nationwide scale. Methods: A register‐based cohort was created consisting of all children in Denmark whose parents were born in 1970 or later by the use of the Danish Civil Registration System. Within this cohort, all groin hernia operations were identified. To establish the risk estimates associated with a positive family history of groin hernia operation, information on groin hernia operations in fathers, mothers and siblings was also assessed. Results: In the cohort of 408 381 persons, a total of 4966 were operated on for groin hernia (incidence rate 2·12 per 1000 person‐years at risk). A person with a mother who had undergone surgery for a groin hernia had an increased risk of 2·89 (95 per cent c.i. 2·48 to 3·34) of having a groin hernia operation; a person with a father operated on for a groin hernia had an increased risk of 1·75 (1·58 to 1·94); and a person with a sibling operated on for a groin hernia had an increased risk of 2·54 (2·17 to 2·96). The strongest association was seen between mothers who had been operated on for groin hernia and their daughters (increased risk 6·01, 95 per cent c.i. 4·53 to 7·80), compared with the risk in girls who did not have a mother who had undergone surgery for groin hernia. Conclusion: Groin hernias are clustered in families, with the strongest relationship seen between mothers and their daughters. Abstract : The aspect of a positive family history of groin hernia has been investigated clinically; however, study heterogeneity and the size of most studies limit consensus regarding the influence of gender and overall inheritance. In a nationwide cohort study from 1977 to 2010 it was found that groin hernias are clustered in families, with the strongest relationship seen between mothers and their daughters. Groin hernias cluster in families